Sex-specific difference in outcome after cardiac resynchronization therapy. (15th January 2019) - Beela, Ahmed S; Duchenne, Jürgen; Petrescu, Aniela; Ünlü, Serkan; Penicka, Martin; Aakhus, Svend; Winter, Stefan; Aarones, Marit; Stefanidis, Evangelos; Fehske, Wolfgang; Willems, Rik; Szulik, Mariola; et al.
Abstract: Aims: Observation of better outcome in women after cardiac resynchronization therapy (CRT) has led to controversies about a potential sex-specific response. In this study, we investigated to which extent this sex-specific difference in CRT outcome could be explained by differences in baseline characteristics between both sexes. Methods and results: We retrospectively analysed data from a multicentre registry of 1058 patients who received CRT. Patients were examined by echocardiography before and 12 ± 6 months after implantation. Response was defined as ≥15% reduction of left ventricular end-systolic volume at follow-up. Patient's characteristics at baseline, including New York Heart Association class, ejection fraction, QRS width and morphology, ischaemic aetiology of cardiomyopathy (ICM), number of scarred segments, age at implantation, atrial fibrillation, and mechanical dyssynchrony (Dyss) were analysed. Patients were followed for a median duration of 59 months. Primary end point was all-cause mortality. Women (24% of the population) had less ICM (23% vs. 49%, P  <   0.0001), less scarred segments (0.4 ± 1.3 vs. 1.0 ± 2.1, P  <   0.0001), more left bundle branch block (LBBB; 87% vs. 80%, P  =   0.01), and more Dyss at baseline (78% vs. 57%, P  <   0.0001). Without matching baseline differences, women showed better survival (log rank P  <   0.0001). After matching, survival was similar (log rank P  =   0.58). In multivariable analysis, female sex was no independent predictor of neither volumetric response ( P  =   0.06) nor survival ( P  =   0.31). Conclusion: Our data suggest that the repeatedly observed better outcome in women after CRT is mainly due to the lower rate ICM and smaller scars. When comparing patients with similar baseline characteristics, the response of both sexes to CRT is similar.